Long-Term Clinical Course of Normal-Tension Glaucoma: 20 Years of Experience - Sang Wook Jin; Seung Yoon Noh (Journal of Ophthalmology)
Purpose. The purpose of this study was to investigate the long-term clinical course of NTG patients who initiated intraocular pressure- (IOP-) lowering therapy. Methods. The present study included 72 normal-tension glaucoma (NTG) patients. The mean deviation (MD) was measured with visual fields. Nocturnal hypotension with weighted standard deviation (wSD) was determined by 24-hour ambulatory blood pressure monitoring. To identify risk factors for NTG progression, linear logistic regression analysis was employed. Results. The mean follow-up period was 21.2 ± 1.1 years. The mean MD progression rate was −0.28 ± 0.24 dB/year. The mean ocular perfusion pressure (OPP) was 52.1 ± 5.9 mmHg. The mean wSD was 14.5 ± 2.2. In the univariate model, disc hemorrhage (RR 7.12; P=0.004), IOP reduction rate (RR 2.12; P=0.045), and OPP (RR 1.94; P=0.027) were associated with glaucomatous visual field progression. However, in the multivariate model, the IOP reduction rate (RR 2.45; P=0.048) and OPP (RR 2.02; P=0.004) were detected to be significant factors associated with progression. Conclusions. The mean rate of visual field progression was −0.28 dB/year in NTG patients treated with medical therapy. The IOP reduction rate and OPP were associated with glaucomatous visual field progression.